Effects of Composite Coatings Functionalized with Material Additives Applied on Textile Materials for Cut Resistant Protective Gloves - Paulina Kropidłowska (MDPI AG, 2021)
The objective of the present work was to evaluate the effects of different types of particles added to a polymer paste applied onto a textile carrier on the cut resistance of the resulting material. Knitted aramid textile samples were coated in laboratory conditions using a polymer paste that was functionalized with 12 types of reinforcing particles of different chemical compositions and size fractions. Cut resistance was tested in accordance with the standard EN ISO 13997:1999 and the results were subjected to statistical analysis. The effects of additive particles on the microstructure of the polymeric layer were assessed by means of scanning electron microscopy. The type and size of the particles affected the cut resistance of the functionalized knitted fabric. They were also found to change the morphology of the porous structure. Composite coatings containing the smallest additive particles exhibited the best cut resistance properties.